Posibles causas de una mortandad de pejerrey, Odontesthes bonariensis, en la Laguna del Monte - Freyre, Lauce Rubén (2005)
Between the 18 and 20 of April of 1998 a silvers side fish kill was observed in Monte urban shallow lake. Rains preceded the phenomenon without being observed lake water level variations, but iridescence in the surface was noticed. Sampled dead fish were obtained for measurement and autopsies were carried out as well. The size range was between 90 and 180 mm of standard length. The fish measurements were made in 21 specimens with best conservation condition and results concerning cephalic index and condition factor were compared with those obtained in previous years. Since most presented high degree of decomposition it was only possible to dissect the gills. Microscopic images of these didn’t record the presence infectious agents so it was discarded as a possible cause. The somatic relationships and indexes show that these fish have suffered growth difficulties which, coupled with the analysis of the gills, supports the hypothesis of an environmental alteration as responsible for the fish kill. Variation leading to an increment in the concentration of organic matter (MO) in the lake produced by the rain induced transport of MO accumulated in the basin of the tributary (channeled), possibly further potentates by the incorporation of hydrocarbons, given the observed iridescence. But this cannot be confirmed by lack of water sample. The made interpretations don’t allow to deduce the cause of the fish kill but enable to point out that the environmental phenomenon that provoked it possibly had not lead to the recorded consequences if the population had been less susceptible, more like under the conditions of previous years.